SISTEM PENUNJANG KEPUTUSAN UNTUK MENENTUKAN PRIORITAS POTENSI DESA MENGGUNAKAN METODE SAW - Anthony Honggo; Dedi Trisnawarman; Zyad Rusdi (Jurnal Ilmu Komputer dan Sistem Informasi, 2018)
Sumbersari Village is a village that located in Moyudan district, Sleman, Daerah Istimewa Yogyakarta, Indonesia. Which is a combination of 3 urban villages in the region of Yogyakarta. Only few information that can be found about Sumbersari village, so the potential of Sumbersari village can not be promoted well. Decision Support System To Determine the Development Priority for Sumbersari Village Potential has a goal to assist village in deciding the potential to be developed.The method used for data collection is literature study and observation. Calculation method that is used in decision support system that will be made is Simple Additive Weighting and programming language used is PHP and database used is MySQL. The design of the application program produces a decision support system that can be used for sorting priorities that displayed in the form of reports and graphs.